The Impact of Lesson Study for Learning Community (LSLC) on Student Participation Based Jigsaw Learning Model - Aziz, Saddam Al; Tasman, Fridgo; Manda, Trysa Gustya; Sari, Shinta (Journal of Learning Improvement and Lesson Study, 2024)
Participation is an important factor in achieving maximum learning in achieving learning goals. However, the level of student participation in learning is still relatively low. Therefore, efforts need to be made in the form of innovation in learning to increase student participation in learning, such as implementing LSLC based on the Jigsaw learning model. This research is a descriptive study with a sample of class XI IPS 1 SMA Adabiah 2 Padang. This research aims to see the impact of LSLC on student participation in learning using the Jigsaw learning model. Based on the results of data analysis, it was found that for each meeting there was a significant increase in student participation. So it can be concluded that learning using LSLC and the Jigsaw learning model has a positive impact on student participation in learning.